Development of an Interactive Android Vocabulary Game ‘FLC’s LevelUp’ Using the ADDIE Model for Beginner Learners at FLC - Zaenul Amri; Aris Sudianto; Muhammad Sulhan Habibi; Muhammad Zamroni Uska (Universitas Medan Area, 2026)
Vocabulary mastery is a crucial foundation for Level 1 students at the Foreign Language Center (FLC). However,conventional methods such as whiteboard writing and rote memorization pose challenges, specifically studentboredom and decreased learning motivation. To address this issue, this study aims to design and develop an interactiveAndroid-based educational game entitled “FLC’s LevelUp!”. The research methodology employed is Research andDevelopment (R&D), adapted into four main stages: architectural research, material collection, data measurement,and data analysis. The results of the functionality testing (Black-Box Testing) achieved a 100% success rate, while theinterface feasibility test using Maze obtained a score of 87/100. These results demonstrate that the game operatesoptimally, is user-friendly, and is capable of fostering a more interactive learning atmosphere. Based on these findings,it can be concluded that the FLC LevelUp! game effectively facilitates students in retaining English vocabulary throughvisual representations and direct in-game interactions. Furthermore, the implications of this study indicate that theutilization of educational games not only assists students but also significantly supports tutors in their instructionalduties, simultaneously serving as a sustainable digital learning media innovation within the FLC environment.